Soft Medical Form with Nanoparticles to Stop Bleeding: Substantiation of Composition and Technology of Obtaining - Yu. N. Barsukova; O. A. Melnikova (Разработка и регистрация лекарственных средств)
Introduction. Due to the growth of general surgical diseases, the treatment and cessation of bleeding is an important problem of medicine and pharmacy. The existing range of hemostatics does not always meet the needs of medical practice and does not provide a wide choice of drugs. Given the great need for drugs to stop bleeding, their development is an urgent task for the modern pharmaceutical industry. One of the promising areas of the creation of dosage forms is the development of hemostatic ointment. Soft dosage forms with optimal rheological characteristics are characterized by a good degree of spreading and easy extrusion of tubes. In the present work, the composition and technology of hemostatic ointment with a nanocomponent was proposed.Aim. Justification of the optimal composition by studying the rheological parameters and the development of technology for producing a soft dosage form with nanoparticles to stop bleeding.Materials and methods. The pharmaceutical substance was aminocaproic acid (FS.2.1.0001.15), iron III chloride (GOST 4147-74), iron oxide nanoparticles (GOST R 57909-2017). The nanoparticles used in this work were obtained by a levitation jet method in a carrier gas medium. The work used technological, physical and chemical research methods. The method of rotational viscometry on the instrument Haake VT550 viscometer is described methodically in detail. Statistical processing of the results was carried out according to the GF XIV methods using standard computer programs.Results and discussion. As a result of the study, it was found that the viscosity of the ointment samples studied gradually decreased with an increase in shear rate, but was non-linear. This dependence is characteristic of systems with a plastic type of flow and characterizes the samples under study as a structured dispersed system. It was also found that the samples of the soft dosage form had thixotropic properties. This in turn serves as an indicator of good lubrication and extrusion of tubes.Conclusion. A production technology has been proposed and a technological scheme for the production of a hemostatic soft dosage form with nanoparticles has been designed.